IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN LEARNING ISLAMIC RELIGIOUS EDUCATION AT THE DRIVING SCHOOL IN SDN SUB-DISTRICT BINAMU DISTRICT JENEPONTO - Rahman, Syahrir; Rusli, Rusli; Palangkey, Rahmi Dewanty (LP2M IAI Al-Khairat Pamekasan, 2025)
The purpose of this study is to describe the teaching modules that have been compiled by Islamic Religious Education teachers. by Islamic Religious Education teachers under the Merdeka Curriculum at Mover School in SDN Binamu District, Jeneponto Regency. To describe the learning process carried out by Islamic Religious Education teachers by the Merdeka Curriculum at the Movers School in SDN Binamu District, Jeneponto Regency. SDN Binamu District, Jeneponto Regency. To describe the assessment of learning carried out by the Islamic Religious Education teacher following the Independent Curriculum at the Movers School in SDN Binamu Subdistrict, Jeneponto Regency. Jeneponto Regency. This study aims to identify the Merdeka Curriculum implemented in Islamic Religious Education learning at the Movers School, and to evaluate the effectiveness of implementing the Merdeka Curriculum in improving the quality of Islamic Religious Education learning, as well as its impact on student learning outcomes, to find out the factors that support and hinder the implementation of the Merdeka Curriculum in the context of Islamic Religious Education learning in these schools, as well as to provide recommendations to schools, educators, and other related parties regarding steps that can be taken to improve the implementation of the Merdeka Curriculum.